The Role of the Constitutional Court in Determining the Police’s Exclusive Jurisdiction through Judicial Review of the Criminal Procedure Code - Dedi Mulyadi; Aurelya Carmenita; Hasna Laksmi Utami; Kaffah Almira Aulia; Mugianing Putri; Nabila Rahma Alia (Journal of Governance and Law Reform, 2026)
ABSTRACT This study examines the role of the Constitutional Court in determining the absolute jurisdiction of the Police through judicial review of the Criminal Code. It aims to analyze the legal reasoning adopted by the Constitutional Court and the implications of its decisions for the authority of the Police within the criminal justice system. This research employs a normative legal research method using statutory, conceptual, and case approaches, with qualitative legal analysis. The findings indicate that the Constitutional Court's decisions play a significant role in providing legal certainty regarding the limits of the Police's absolute jurisdiction while reinforcing the principle of constitutionality in the exercise of law enforcement authority. The study concludes that judicial review conducted by the Constitutional Court serves not only as a mechanism for examining the constitutionality of statutory provisions but also as an important instrument for clarifying the distribution of authority among law enforcement institutions. Consequently, the Court's decisions contribute to greater legal certainty, the protection of citizens' constitutional rights, and the effectiveness of Indonesia's criminal justice system.